2022
DOI: 10.1021/acs.jpcb.2c04325
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Polymer Chains in Poly(ethylene oxide)/Silica Nanocomposites via a Combined Computational and Experimental Approach

Abstract: The dynamics of polymer chains in poly­(ethylene oxide)/silica (PEO/SiO2) nanoparticle nanohybrids have been investigated via a combined computational and experimental approach involving atomistic molecular dynamics simulations and dielectric relaxation spectroscopy (DRS) measurements. The complementarity of the approaches allows us to study systems with different polymer molecular weights, nanoparticle radii, and compositions across a broad range of temperatures. We study the effects of spatial confinement, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…30 Details of the simulation model and the equilibration protocol are given elsewhere. 31 Initial atomistic PEO/SiO 2 configurations at a high temperature (T = 400K) were obtained from a previous work. 31 The models were afterward subjected to MD cooling steps of 10 K in the isobaric-isothermal ensemble down to T = 150 K. For each of the investigated systems, cooling was performed for 3 uncorrelated configurations to improve statistics.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Details of the simulation model and the equilibration protocol are given elsewhere. 31 Initial atomistic PEO/SiO 2 configurations at a high temperature (T = 400K) were obtained from a previous work. 31 The models were afterward subjected to MD cooling steps of 10 K in the isobaric-isothermal ensemble down to T = 150 K. For each of the investigated systems, cooling was performed for 3 uncorrelated configurations to improve statistics.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…31 Initial atomistic PEO/SiO 2 configurations at a high temperature (T = 400K) were obtained from a previous work. 31 The models were afterward subjected to MD cooling steps of 10 K in the isobaric-isothermal ensemble down to T = 150 K. For each of the investigated systems, cooling was performed for 3 uncorrelated configurations to improve statistics. At each cooling step, MD runs of 10 ns were performed, after the first 5 ns of which the potential energy and the specific volume of the system were stabilized.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium structural and dynamic properties of PEO/SiO 2 systems have been extensively examined by both simulations 28,62,84−86 and experiments. 28,85,87,88 Our methodology for probing the distribution of local mechanical properties is based on a recent multiscale computational approach computing effective (per atom) stress and strain fields within atomistic model PNCs under an applied external field. 65,89 In the rest of the paper, we provide in Section 2 details about the model systems and the simulations focusing on the deformation process and the way we compute the local stress and strain fields.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalizing nanoparticles through chain adsorption or grafted nanoparticles is a common strategy to control particle dispersion in polymer nanocomposites and their structure, dynamics and mechanical properties have been extensively investigated. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Relating the particle dynamics to the dynamics of polymer grafted chains has importance in understanding the composite dynamics; however, it can only be attained for matrix-free composites. The recent simulation study on grafted particles in unentangled matrixes showed that relaxations of monomers close to particle surfaces are slower than the chains farther away due to graft chain constraints and the confinement of neighboring chains.…”
Section: Introductionmentioning
confidence: 99%